Three-dimensional plant modeling and simulation: mow far does recent computer technology expand to assist the landscape architecture practice - Yusof, Hanita (2008)
There are some contradict perceptions on the issue of advance digital application related to landscape architecture field. Either there is no advance digital application being invented for landscape architectural design purposes or another perception that there are probably few applications related to landscape architecture field but not being utilized by landscape practitioners in landscape design practice. This particular research topic on 'threedimensional plant modeling and simulation: how far does recent computer technology expand to assist the landscape architecture practice' will answer the perceptions based on literature studies done by researchers all over the world as well as the recent information by the vendors which both related to this research topic will finally reveal the actual situation